1994
DOI: 10.1590/s0004-282x1994000400004
|View full text |Cite
|
Sign up to set email alerts
|

Sleep polygraphic parameters in neuromuscular diseases

Abstract: In a polysomnographic study of 32 neuromuscular patients-22 with a form of muscular dystrophy, 3 with a form of congenital myopathy, 4 with a form of spinal muscular atrophy, 1 with a recurrent form of polymyositis and 1 with osteogenesis imperfecta syndrome--of which 21 were nonambulatory, we observed sleep related respiratory disturbances represented by: drops in oxygen saturation (SaO2), cardiac arrhythmia, sleep disruption, apneas, tachypnea, tachycardia and snoring. Nine out of the cohort of 32 patients p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…There are very few studies of sleep patterns in patients with SMA, and especially in subjects with SMA1 [9]. In a polysomnographic (PSG) study of 32 neuromuscular patients, four with a form of SMA sleep architecture revealed an increase in stage 1 sleep coupled with a decrease or absence of rapid eye movement (REM) sleep [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are very few studies of sleep patterns in patients with SMA, and especially in subjects with SMA1 [9]. In a polysomnographic (PSG) study of 32 neuromuscular patients, four with a form of SMA sleep architecture revealed an increase in stage 1 sleep coupled with a decrease or absence of rapid eye movement (REM) sleep [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sleep latency was found to be significantly prolonged in SMA type 1 patients, but no data are available regarding sleep latency in SMA type 2 and 3 ( 42 ). Regarding NREM sleep, N1 and N2 were increased in SMA type 1, and stages N1was increased in SMA type 2 ( 24 , 41 , 42 ), while slow-wave sleep (sleep stage N3) were decreased ( 42 ). However, stage N2 sleep proportion is found to be lower in SMA type 1 compared to types 2–3, and stages N1-3 increased parallelly with age ( 34 ).…”
Section: Respiratory Function and Sleep In Smamentioning
confidence: 95%
“…Indeed, very few studies investigated sleep patterns in patients with SMA. Scattered reports of a few patients revealed a decrease or absence of REM sleep together with an increase of stage 1 sleep in SMA patients ( 41 ). Furthermore, sleep latency was found to be significantly prolonged in SMA type 1 patients, but no data are available regarding sleep latency in SMA type 2 and 3 ( 42 ).…”
Section: Respiratory Function and Sleep In Smamentioning
confidence: 99%
“…Buna ek olarak, REM uyku evre süresinde artış da bildirilmiştir (10). SMA tip 1 ve tip 2 hastalarında da UE'de azalma ile birlikte, yüzeyel uyku evre sürelerinde (N1 ve N2) artış, ve REM uyku evre sürelerinde ise azalma bildirilmiştir (11)(12)(13)(14)(15). Bizim çalışmamızda ise, DMD tanısı alan hastalarda uykunun makro yapısı incelendiğinde, aynı yaş grubundan oluşan sağlıklı kontrol grubuna kıyasla, REML uzun ve toplam REM uyku evre süresinin kısa olduğu izlendi; ancak bu fark istatistiksel anlamlı değere ulaşmadı.…”
Section: Sonuçunclassified